Students in Canada and the Czech Republic - socioeconomic factors and their impact - Hellingman, Sean (2018)
This thesis examines the choices of individuals with respect to higher education in the Czech Republic and Canada. Specifically, how does the students’ socioeconomic backgrounds influence their study decisions. Data from the Czech The European Union Statistics on Income and Living Conditions survey and the Canadian Survey of Labour and Income Dynamics were used to identify and quantify the magnitude of the influences of students’ entry to university. Furthermore, data from the Czech EUROSTUDENT and the Canadian National Graduates Survey was used to see how students and graduates’ socioeconomic backgrounds influenced their choice in study field. Individuals from more households with higher socioeconomic status were more likely to enter university than people who were less well off in both countries. However, the impact of this social selectivity seems to differ between the two nations. The choice of study field is significantly influenced by the individual’s socioeconomic background in similar ways in both nations. Social selectivity is ever present in higher education in the Czech Republic and Canada.